Heterogeneity in Earning Management of Listed Companies Following International Financial Reporting Standards Convergence: A Developing Country Experiences - Weerathunga, P. R.; Xiaofang, Chen; Sameera, T. K. G. (International Journal of Economics and Financial Issues, 2019)
This study examines the earning management behavior of Sri Lankan firms following IFRS convergence. Moreover, we investigate whether the earning management following IFRS convergence is similar across different companies. We separately evaluate the companies based on size, auditor type, and performance to see whether these factors can moderate earning management behavior. We collected the data from a sample of 160 companies that are listed on the Colombo Stock Exchange (CSE) for the period spanning from 2008 to 2015. The period from 2008 to 2011 was the pre-IFRS convergence and the period after 2012 was the post-IFRS period. Following prior studies, we used several measures to capture the earning management around IFRS convergence. Especially, our measures aim to identify earning smoothing and managing towards earning target and thereby determining whether the firms have engaged in earning management and its increase and decrease. The results show that the earning management, in overall, has not decreased following IFRS convergence. However, our results indicate that the post-IFRS earning management is vary between companies. That is, large companies and companies with big four auditors experienced a decrease in earning management following IFRS convergence. Similarly, certain aspects of earning management of high performing companies is also found to have decreased in post-IFRS convergence. Finally, our findings provide important implications for regulators, investors and other corporate stakeholders. Keywords: Earnings Management, IFRS Convergence, Sri Lankan Firms JEL Classifications: M410, M480, C2, C3 DOI: https://doi.org/10.32479/ijefi.8872